Pengaruh Mobilitas Penduduk terhadap Pengembangan Wilayah Kota Serang - Rico Permana Jovi; Muhamad Nabil (PT. Hasba Edukasi Mandiri, 2026)
The high population mobility due to the designation of Serang City as the capital of Banten Province has triggered complex dynamics in regional development, affecting spatial structure, economic growth, and infrastructure burden. This qualitative library research aims to analyze the patterns, impacts, and gaps between planning and reality of regional development in Serang City due to population mobility. The results show three dominant patterns: permanent migration, daily commuters (15,000 people/day), and seasonal circulation. Positive impacts include the growth of the trade sector by 9.4% per year and the emergence of new economic centers. However, negative impacts include severe congestion (LOS E-F), clean water coverage of only 62%, overcapacity of the Bagendung landfill (380 tons/day vs. 250 tons capacity), and spatial planning implementation gaps where the 30% public green space target is only achieved at 12.6%. Comprehensive short-term, medium-term, and long-term strategies based on cross-regional collaboration and adaptive spatial planning revision are urgently needed. Population mobility can become an asset for regional development if managed with appropriate and sustainable policies.